Synthesis and Study of Many New Chalcone Derivatives - Natiq G. Ahmad; Murtatha H. Ali (College of Education for Pure Sciences, 2018)
This study include the synthesis of the compound 1-(1H-benzo[d]imidazol-2-yl)ethanol [1], from the reaction of ortho pheneylene diamine with lactic acid and then oxidized using potassium dichromate to give1-(1H-benzo[d]imidazol-2-yl) ethanone [2]. Reaction of this compound with different substituted benzaldehydes or 1-(1H-benzo[d]imidazol-2-yl)ethanone, to obtain α, β-unsaturated carbonyl compounds (chalcones) [3-11]. These chalcones have been used in preparing number of heterocyclic compounds through reaction with the hydrogen peroxide to get the oxiran compounds (three membered rings) [12-20], hydroxyl amine hydrochloride to prepare the isooxazoline compounds(five membered rings) [21-29], 3-nitrobenzohydrazide to prepare the pyrazoline compounds(five membered rings)[30-38], thiosemicarbazide hydrochloride to prepare the pyrazoline compounds(five membered rings) [39-47], semicarbazide to prepare the pyrazoline compounds(five membered rings) [48-56], guanidine nitrate to prepare the pyrimidine compounds(six membered rings) [57-65], ortho pheneylenediamine to prepare the benzodiazepine compounds (seven membered rings) [66-74], ortho aminophenol to prepare the benzoxazepine compounds(seven membered rings) [75-83]. The synthesized compounds were identified, using chemical, physical and spectral methods (melting points, color change, infrared spectra, ultraviolet spectra, nuclear magnetic resonance spectra and many theoretical studies).